Impact Of Business Intelligence (Bi) Capabilities On Organizational Performance: Bi System Success As Mediator And Information Technology Governance As Moderator - Phan, Koo Yuen (2023)
In today’s dynamic business environment in the Industry 4.0 era, optimising organisational performance is a critical concern for business organisations, particularly Malaysian Public Listed Companies (PLC). However, organisational performance at PLC has been on a downward trend since 2018. Business Intelligence (BI) capabilities are therefore considered as one of the key components that enables organisational performance. Successful BI systems with the right capabilities deployed can help organisations predict changes in the internal and external environment. In this study, Resource-based View (RBV) and Dynamic Capabilities View (DCV) theories were used along with the DeLone and McLean Information System (D&M IS) success theories, an integrated framework developed to examine the impact of BI capabilities on the organisational performance of Malaysian PLC via BI systems success as mediator and IT governance mechanisms (ITG) as moderator. 223 responses were collected via the questionnaire survey method with only 207 qualified as valid responses for analysis. SmartPLS was used to conduct hypothesis testing for hypotheses H1 to H20. Overall, the results showed all twenty hypotheses were supported in this study. Theoretically, this study confirmed the robustness of these integrated three theories, which helped to better understand the importance of BI resources in improving the success of BI systems and organisational performance.